2015
DOI: 10.1136/sextrans-2015-052034
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections associated with alcohol use and HIV infection among men who have sex with men in Kampala, Uganda

Abstract: Objectives Few studies have been conducted in Africa to assess prevalence of sexually transmitted infections (STIs) and risk factors among men who have sex with men (MSM). We report findings from the first behavioural survey to include STI testing among MSM in Kampala, Uganda. Methods Respondent-driven sampling (RDS) was used to recruit MSM for a biobehavioural survey. Eligible participants were men who reported anal sex with another man in the previous 3 months, were 18 years or older, and resided in Kampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
(16 reference statements)
7
31
1
Order By: Relevance
“…With two exceptions, 30,31 alcohol or drug use was not the primary focus of these studies. Studies included diverse MSM populations [e.g., male sex workers, 32 MSM living with HIV, 33 gay, lesbian and bisexual persons, 34 and participants in a pre-exposure prophylaxis (PrEP) trial 35 a few studies exclusively surveyed substance users.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With two exceptions, 30,31 alcohol or drug use was not the primary focus of these studies. Studies included diverse MSM populations [e.g., male sex workers, 32 MSM living with HIV, 33 gay, lesbian and bisexual persons, 34 and participants in a pre-exposure prophylaxis (PrEP) trial 35 a few studies exclusively surveyed substance users.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, almost two-thirds of men in a Kenyan study 43 and 82.5% in a study in Botswana 39 reported having used alcohol in that period. Using alcohol once or more than once a week in the past month was reported by 61.7% and 67.5% among men in Uganda 31 and Cote d’Ivoire. 44 Chapman et al 45 reported that 22.4% of the studied MSM in Rwanda drank alcohol every day in the past month.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If you look through our archive, you will find many examples of research from “difficult” settings—such as our blockbuster special issue on Middle East and North African research in 2013 7. We are delighted this month to publish a population based survey on STI related symptoms from Iran,8 a report on STI and HIV in MSM from Uganda,9 and an exploration of rectal microbicide preferences in Peruvian MSM 10…”
mentioning
confidence: 99%